The ‘Thaharah Bermakna’ Training Through The Logo Analysis Model to Build Students’ Positive Characters - Nurjannah Nurjannah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This experimental study aimed to investigate the effect of the ‘thaharah bermakna’ (meaningful purification)’ through the logo analysis model to build students’ positive characters. The experiment employed the one-group pretest-posttest design involving 22 students of SMP Diponegoro Yogyakarta. The data were collected through a positive character scale (ri = 0.316-0.651, α = 0.929) and a monitoring sheet for the ‘thaharah bermakna’ independent practice. The results of the within subject test showed that the ‘thaharah bermakna’ training and the independent practice for a week were capable of significantly improving students’ positive characters with F = 0.578, p = 0.005 (p<0.010). Before the treatment, the subjects’ mean score was 186.91 and after the treatment their mean score improved to 193.91. The study concluded that the ‘thaharah bermakna’ training through the logo analysis model and an independent practice for a week significantly improved students’ positive characters. In other words, it could be said that the ‘thaharah bermakna’ training was effective to build students’ positive characters.